Dewetted Au films form a highly active photocatalytic system on TiO2 nanotube-stumps - Yoo, Jeong Eun; Lee, Kiyoung; Schmuki, Patrik (Electrochemistry Communications, 2013)
Highly ordered TiO2 nanotube stump-[TiO2 NS]-layers, prepared by anodization of Ti in HF/H3PO4 solutions, were used as a substrate for a thermal dewetting of Au thin films. Depending on the initial Au sputter-deposited layer thickness, various sizes and densities of gold nanoparticles [Aunp] could be obtained on the TiO2 NS. Under certain conditions, very homogeneously distributed Aunp (with diameters in the range of 2–15 nm) can be generated. Such Aunp/TiO2 NS combinations show a high efficiency for H2 production from H2O/EtOH solutions. A maximum H2 production efficiency could be obtained from a 2 nm thick Au layer (57.03 extgreekml H2 for 9 h) that was dewetted to ≈ 28,000 particles/ extgreekmm2 with individual particle diameters of ≈ 5 nm.
EAM Import::2019-03-13